Patency of small laser iridotomy evaluated using anterior-segment optical coherence tomography - Nakabayashi S (Dove Medical Press, 2014)
Seigo Nakabayashi, Motofumi Kawai, Toru Yamaguchi, Akitoshi Yoshida Department of Ophthalmology, Asahikawa Medical University, Asahikawa, Japan Abstract: We report the case of a patient with recurrent acute angle-closure glaucoma who had undergone a previous laser iridotomy. Because the initial iridotomy was small, patency could not be determined by slit-lamp examination. Therefore, anterior-segment optical coherence tomography was used to evaluate the patency. Cross-sectional images showed the presence of a membrane with an anterior bowing configuration at the base of the iridotomy, suggesting that recurrent pupillary block was the causative mechanism. A repeat laser iridotomy was performed, with a resultant decrease in the intraocular pressure and widening of the anterior chamber angle. Anterior-segment optical coherence tomography may be helpful to confirm the status of a laser iridotomy, especially when the iridotomy is small. Keywords: anterior-segment optical coherence tomography, laser iridotomy, acute angle-closure glaucoma